Clinical implications of DNA ploidy, stroma, and nucleotyping in predicting peritoneal metastasis risk for gastric cancer - Jingwen Yuan; Yue Jiang; Fangfang Chen; Tian Li; Zhi Zeng; Shasha Ruan; Junfeng Yan; Jiatong Lu; Qiang Li; Jingping Yuan; Qiang Tong (BMC Cancer)
Abstract Background Gastric cancer peritoneal metastasis lacks effective predictive indices. This article retrospectively explored predictive values of DNA ploidy, stroma, and nucleotyping in gastric cancer peritoneal metastasis. Methods A comprehensive analysis was conducted on specimens obtained from 80 gastric cancer patients who underwent gastric resection at the Department of Gastrointestinal Surgery of Wuhan University Renmin Hospital. Tumor tissues were sectioned and stained. DNA ploidy, stroma, and nucleotyping were quantified using microscopy and digital analysis software. Data analysis was employed by Pearson Chi-square, continuous correction Chi-square, and binary logistic regression. Results Using both univariate and multivariate analysis, pathological T stage and nucleotyping exhibited a positive correlation with peritoneal metastasis. DNA ploidy and stroma showed a positive correlation in univariate analysis. Chi-square tests demonstrated a positive correlation of DNA ploidy, stroma, and nucleotyping with peritoneal metastasis. The combined application of these three indicators displayed heightened predictive value for peritoneal metastasis. Non-diploid status, high stroma, and chromosomal heterogeneity emerged as positive factors for peritoneal metastasis in gastric cancer. Conclusions DNA ploidy, stroma, and nucleotyping prove to be predictive factors for peritoneal metastasis, with enhanced predictive efficacy when combined in pairs.